Revision of Gastric Plication to Gastric Bypass (Indications and Solutions) - Al-Sewadi, Wisam Hamza; Algazgooz, Falih M.; Abdullah, Nawal; Fadhl, Jawad Ramadhan (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Laparoscopic gastric plication (LGP) has gained increased acceptance as initial weight loss operation, but as with any other procedures, insufficient weight loss, early and late complications such as early and late strictures, gastroesophageal reflux and leak and others have been announced as an indication for revision to gastric bypass surgery as the correct solution. AIM: The aim of the study was to recognize the common indications for revision of gastric plication (GP) to RYGP and OAGB in our centers and to evaluate the outcome of treating weight regain, complications, and comorbidities. METHODS: A retrospective study conducted on 54 cases of undesirable results following gastric plication in other centers that were revised to gastric bypass procedures (RYGB and OAGB) from June 2015 to June 2018. Weight regain, gastroesophageal reflux disease not responding to medical treatment, undiagnosed hiatal hernia at surgery, post-operative leak, and strictures are the main categories included as indications for revision to gastric bypass in this study for a period of follow up to 2–5 years regarding weight loss, improvement of GERD and hiatal hernia, improvement of leak, stricture, and axial rotation of stomach. RESULTS: 54 consecutive patients included in this study previously subjected for LPG few years ago. 13 (24%) male and 41 (76%) female patients with mean age of 39.5 years ranging from (21–58) years and BMI from (41–48) Kg/m2. The main indication for revision surgery in the form of gastric bypass procedure (RYGB and OAGB) was weight regain in about 69% of cases. In addition to non-responding GERD to medical treatment (13%), hiatus hernia with plicated stomach migration to the mediastinum (3.7%), local collection secondary to leak (1.85%), stricture at site of plication (1.85%), and one case of axial rotation of the stomach (1.85%). Patient postoperatively done well and a follow-up for up to 3 years after revision surgery was uneventful. Most of our patients have good improvement regarding the inclusion criteria in our study (100% cured GERD, 90% cured leak site, about 90% cured symptomatic and radiological hiatal hernia, 100% cured after early, late strictures, and axial rotation while regarding loss of weight and least comorbidities about 88%). CONCLUSION: Although GP is an established bariatric procedure in treating and solving obesity and its complications, there are certain restrictions and difficulties that makes RYGB superior to GP.